1860. Small State, Big Collaboration: Creation of First New Hampshire Statewide Antibiogram Guides Stewardship Efforts. (26th November 2018) - Leeman, Hannah; Chan, Benjamin; Hansen, Katrina; Talbot, Elizabeth; Zimmermann, Carly; Calderwood, Michael; Dave, Apara; Santos, Paul
Abstract: Background: Antibiotic-resistant infections have been identified as an urgent national health threat. In response, the New Hampshire Division of Public Health Services (DPHS) sought to develop a system for tracking antibiotic resistance statewide through use of hospital antibiograms to (1) proactively monitor resistance trends over time and geographic region, (2) promote antimicrobial stewardship in NH healthcare facilities, and (3) provide a tool for providers to help guide appropriate antibiotic prescribing. Methods: Through statutory legislative authority, DPHS requires hospital laboratories to report antibiogram data annually. DPHS formed an advisory group, consisting of infectious disease, medical and pharmacy subject matter experts to develop a standardized data collection tool. DPHS validated reported data to confirm accuracy, and clarify aberrant data by comparing the susceptibilities among all hospitals. Any questionable data were verified with the respective laboratory. The combined data were reviewed by the clinical advisory group and recommendations were created from the antibiogram data to highlight appropriate antibiotic prescribing and the need for coordinated stewardship. The antibiogram and clinical recommendations were disseminated widely throughout the state. Results: All 26 hospitals in New Hampshire submitted data. A total of 42, 519 and 21, 306 bacteria were cultured from urine and non-urine sources, respectively. The clinical advisory group's recommendations included interpretations and antibiotic therapy directives for common clinical syndromes. Dissemination was accomplished through a health alert, partnership with a state working group of stakeholders, widespread email communication and online publication. Conclusion: The small size of New Hampshire, centralized public health structure, and close working relationships with all hospitals allowed for efficient collection of these data. Our process may serve as a model for other states, and will inform more accurate, comprehensive antibiotic resistance surveillance. This antibiogram is the launch for a larger statewide public health antibiotic stewardship campaign and coincides with national efforts around antibiotic stewardship and resistance surveillance. Disclosures: All authors: No reported disclosures.